Corporate liability for transboundary environmental harm : an international and transnational perspective - Gailhofer, Peter; Krebs, David (Lawyer); Proelss, Alexander; Schmalenbach, Kirsten; Verheyen, Roda (Springer, 2023)
"This book aims to elaborate on the legal prerequisites to establish the liability of corporations for transboundary environmental harm, not only by identifying existing liability rules, principles, and standards but also by analysing their potential for further legal development. The authors consider international and transboundary liability law to currently be an underutilised tool for international environmental protection. The book seeks to address this by exploring what is needed in terms of legislative action and identifying options for judicial pliability, thereby providing an important legal contribution in furthering the development of an effective international and transnational environmental liability law regime"--Publisher's description.
Keywords: Liability for environmental damages.; Environmental law, International.; Transboundary pollution -- Law and legislation.; Responsabilité pour dommages à l'environnement.; Environmental law, International; Liability for environmental damages; Transboundary pollution -- Law and legislation; Environmental Harm; Civil Liability; Corporate Liability; International Liability; Supply Chains; Climate Litigation; Duty of Care; Geoengeneering; Electronic book.